Evidence for Conservative Treatment of Adolescent Idiopathic Scoliosis – Update 2015 (Mini-Review) - SY, Ng; Bettany-Saltikov, Josette; Moramarco, Marc (Current Pediatric Reviews, 2016)
Idiopathic scoliosis predominantly afflicts adolescents. Adolescents with mild curvatures do not generally have any symptoms. However spinal fusion is indicated when the deformity exceeds 45°. Treatment is thus necessary to prevent and/or reduce the progression of curvatures to that below which surgery is indicated. Conservative treatment of adolescent idiopathic scoliosis includes observation, scoliosis-specific exercises (SSE) and bracing. There is increasing evidence suggesting that SSE and brace treatment can significantly limit the progression of spinal curvatures. In growing adolescents with curvatures more than 20°, bracing is indicated and should be used in conjunction with SSE. The effectiveness of bracing varies according to the type of brace applied to the patient. In general rigid braces are preferable to soft flexible braces, as the latter falls short of halting curvatures progression. Also, preliminary evidence suggests that asymmetric braces which enable over-correction provide more correction when compared with symmetrical braces. Recently it has also been reported that high quality bracing can also reduce curvatures exceeding 45° in over 70% of growing adolescents. This new knowledge might possibly increase the threshold of surgical indications to beyond 50o or above in the near future.
Keywords: Chêneau brace